2012
DOI: 10.1073/pnas.1115967109
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stress-activated integrin α5β1 induces opening of connexin 43 hemichannels

Abstract: The connexin 43 (Cx43) hemichannel (HC) in the mechanosensory osteocytes is a major portal for the release of factors responsible for the anabolic effects of mechanical loading on bone formation and remodeling. However, little is known about how the Cx43 molecule responds to mechanical stimulation leading to the opening of the HC. Here, we demonstrate that integrin α5β1 interacts directly with Cx43 and that this interaction is required for mechanical stimulation-induced opening of the Cx43 HC. Direct mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
208
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(220 citation statements)
references
References 35 publications
9
208
0
3
Order By: Relevance
“…Moreover, they are triggered to open by some stimulation, such as inflammation, mechanical stress or ischemia (Batra et al, 2012;Johansen et al, 2011;Karpuk et al, 2011). In our study, however, we demonstrated for the first time that connexin-mediated hemichannels are responsible for glucose uptake in OPCs, implying a role for oligodendroglial connexin hemichannels under physiological conditions.…”
Section: Inhibition Of Hemichannel Activity Impacts Opc Proliferationmentioning
confidence: 61%
“…Moreover, they are triggered to open by some stimulation, such as inflammation, mechanical stress or ischemia (Batra et al, 2012;Johansen et al, 2011;Karpuk et al, 2011). In our study, however, we demonstrated for the first time that connexin-mediated hemichannels are responsible for glucose uptake in OPCs, implying a role for oligodendroglial connexin hemichannels under physiological conditions.…”
Section: Inhibition Of Hemichannel Activity Impacts Opc Proliferationmentioning
confidence: 61%
“…via conformational changes, which could be induced by mechanical stimuli (55)(56)(57). The conformational activation of integrin ␣5␤1 might also play a crucial role in the process of ESW-induced adhesion and migration of osteoblasts.…”
Section: Journal Of Biological Chemistry 26207mentioning
confidence: 99%
“…We have previously shown that FFSS increases the assembly and cell surface expression of Cx43 HC (Siller-Jackson et al, 2008). We recently demonstrated that integrin a5 interacts with Cx43 in osteocytic cells and this interaction, in conjunction with the activation of integrin a5, is required for the opening of Cx43 HC in response to mechanical loading (Batra et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%